Criminal Sanctions for Corruption Crimes Based on Perspective Study of Renewal Law and the Relationship with Islamic Criminal Law - Wahyuni, Fitri; Ishaq, Ishaq; Irawan, Aris (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2021)
The crime of corruption is an extra ordinary crime that damages the joints of the economy in a country. Therefore, the crime must be given a sanction that creates a deterrent effect so that the act can be minimized. However, in reality the sanctions against corruption crimes that have been drafted at this time in Indonesia need to be reformulated through the reform of criminal law in Indonesia. This study examines the granting of criminal sanctions for perpetrators of corruption according to Islamic Criminal Law in relation to Criminal Law Reform. The research method used is normative legal research, with data sources in the form of secondary data and primary, secondary and tertiary legal materials. The analysis is in the form of descriptive qualitative. The criminal sanctions for perpetrators of corruption in Indonesia as stipulated in the corruption crime law are only in the form of imprisonment and fines. Thus, there is a need for reform of criminal law, specifically criminal law for corruption. These legal reform efforts sometimes originate from living laws besides Islamic law, including customary law as law that was applicable in Indonesian society before the entry of the Dutch criminal law. Therefore, the renewal of criminal sanctions for perpetrators of corruption crimes is currently a matter that needs to be reformulated considering the current sanctions have not provided a deterrent effect for perpetrators of corruption by reforming the law and incorporating Islamic values into the formulation of these sanctions, especially the values of justice in Islamic criminal law.